2002
DOI: 10.1046/j.1442-2050.2002.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transhiatal resection of epiphrenic diverticulum

Abstract: Our experience with videolaparoscopic operations for hiatus hernia and achalasia, which have almost replaced classical procedures, enabled us to use the same technique for other interventions in the distal third of the thoracic esophagus. Thus, we were able to treat epiphrenic diverticulum using a minimally invasive approach. We report our experience with videolaparoscopic diverticulum resection. The procedure was performed in three patients, all of them elderly men with ventilation limitation and a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…The transhiatal approach might increase the risk of tearing the adherent lung and the subsequent development of pneumothorax in our present case. Thoracoscopic approach to the diverticulum necessitates the use of an open-jaw endostapler [16][17][18][19][20][21][22]; this may be related to a risk of leak at the staple lines as a result of incomplete staple line closure. In some cases, the muscular layers were closed over the staple line [9,23], but this step sometimes has not been done if it was considered unnecessary [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…The transhiatal approach might increase the risk of tearing the adherent lung and the subsequent development of pneumothorax in our present case. Thoracoscopic approach to the diverticulum necessitates the use of an open-jaw endostapler [16][17][18][19][20][21][22]; this may be related to a risk of leak at the staple lines as a result of incomplete staple line closure. In some cases, the muscular layers were closed over the staple line [9,23], but this step sometimes has not been done if it was considered unnecessary [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…Definite treatment for epiphrenic diverticulum consists of left thoracotomy, diverticulectomy, esophageal myotomy, and partial fundoplication. Recently, many studies reported laparoscopic epiphrenic diverticulectomy with myotomy and antireflux procedure to be as safe and effective as the traditional approach [30][31][32][33][34][35][36][37]. Laparoscopic resection offers superior visualization and access and avoids the major incision necessary in open procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic recurrence rates after laparoscopic diverticula repair seem to be high compared with earlier studies of open repair. The long-term consequences of anatomic recurrence are currently uncertain [33][34][35][36][37]. The prognosis for patients with carcinoma in an esophageal diverticulum is poor [21] because the cancer is usually discovered at an advanced stage, most symptoms are intermittent and related to underlying dysmotility, and progress is insidious.…”
Section: Discussionmentioning
confidence: 99%
“…Müller und Halbfass weisen richtigerweise darauf hin,dass diese Problematik in der deutschsprachigen Literatur kaum erwähnt wird.In neueren Arbeiten [3,4] beträgt die Leckagerate allerdings 10-33% und stellt somit durchaus ein relevantes Problem dar. Der Gedanke ist naheliegend, deshalb auf die komplikationsträchtige Exzision des Divertikelsackes zu verzichten und nur die auslösende Ursache zu beseitigen.Diese liegt nach allgemeinem Verständnis in einer inadäquaten bzw.…”
unclassified
“…Müller und Halbfass weisen richtigerweise darauf hin,dass diese Problematik in der deutschsprachigen Literatur kaum erwähnt wird.In neueren Arbeiten [3,4] Allerdings liegen die Verhältnisse beim epiphrenischen Divertikel anders: Auch wenn der "Auslasswiderstand" der distalen Speiseröhre bzw.des unteren Ösopha-gussphinkters durch die Myotomie beseitigt wird, wird dadurch nicht die Schwelle zwischen dem Divertikel-und Ösopha-guslumen beseitigt.Auch nach Myotomie kommt es zu keiner Rückbildung des Divertikelsackes, so dass kaum zu erwarten ist, dass die Depot-und Regurgitationssymptome gebessert werden.Müller und Halbfass stellen heraus,dass bei ihren Patienten die Dysphagie mit Gewichtsverlust das Leitsymptom war und dass diese auch ohne Divertikulektomie erfolgreich behandelt werden konnte.…”
unclassified